Evaluation of Water Needs and Availability in The Design of The Water Needs Masterplan on The IPDN West Sumatera Campus - Fauzi, Fauzi; Istijono, Bambang; Hidayat, Benny (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The sustainable availability of clean water is crucial for supporting academic, residential, and institutional operational activities in higher education settings. In general, previous research has primarily focused on clean water planning at the city or regional level, without examining the need and availability of water on boarding campuses that have distinct consumption patterns and distribution systems. This research aims to fill the gap by conducting an integrated evaluation of water needs and availability, serving as the basis for preparing a water management master plan at the West Sumatra IPDN Campus. A mixed-methods approach is employed, combining quantitative analysis based on SNI 03-7065-2005 to estimate water needs with qualitative analysis of infrastructure conditions and water quality through field surveys, interviews, and laboratory tests. The results showed that the water demand reached 92,150 liters/day (1.1 liters per second), while the source capacity was 5.03 liters per second, resulting in a surplus of 1,839%. Although the water supply was quantitatively adequate, quality tests revealed turbidity and bacteriological contamination at some distribution points, attributed to the corrosion of galvanized pipes and the absence of secondary filtration. This confirms that sufficient quantity does not guarantee the quality and efficiency of distribution. Therefore, network modernization, the implementation of layered filtration, and periodic monitoring are necessary. This research contributes to the development of a sustainable campus water management model in Indonesia.